A Study on effectiveness of policy support for SME's export - KIM, Heeran (KDI School, 2016)
This paper aims to analyze the effectiveness of policy support for SME's export. Since domestic market is already limited and the competitiveness with large enterprises is getting severe, the export expansion is indispensable to improve the growth potential of SMEs. Since SMEs play an important role in the Korean economy, it is necessary to support the export expansion to improve the growth potential of SMEs as well as job creation. To expand the export assistance programs by the Korean government, the effectiveness of SME export support policy should be proved. For this purpose, OLS (Ordinary Least Squares) regression is applied to 2,439 SMEs including the treatment group of 578 and the control group of 1,861. It observedwhether the policy support is directly effective on SME's export, the variable of 'subsidy', which SMEs receive from the government, is included as an independent variable with that of 'export growth', which is the growthrate of SME's export, as a dependent variable. As a result, the policy support for SMEs have a positive impact on export with a statistically significance at the 10% level. Thus, export is the effective means to improve the growth of SMEs.
Thesis(Master) --KDI School:Master of Development Policy,2016